Direct Production Cost Improvements at PT. Freeport Indonesia's Concentrating Division - Pramono, Karel Yudi; Simatupang, Togar M (The Indonesian Journal of Business Administration, 2015)
AbstractIn an perfect competition market such as one within the mining and metals industry, gaining competitive advantage through production efficiency and cost efficiency is crucial. At PT Freeport Indonesiaâ€™s Concentrating division, where the beneficiation process from ore to concentrate is being done, cost control is a big driver to ensure maximum profitability for the company. Unfortunately, it has been identified that from 2009 to 2013, direct production cost within the division has increased by 29.3% at a time where production had declined by 26% and metal prices were also on the decline. A simple Pareto chart analysis was able to identify major cost elemet contributors to the increased expenses. Further detailed analysis using Failure Mode and Effects Analysis (FMEA) within a Focus-Group-Discussion (FGD) forum was done to identify deficiencies within the business processes related to those major contributors. Eight root causes of process deficiencies were identified through this analysis, which cumulatively contained an opportunity to save USD11.2million per year on cost. Eight concurrent solutions were proposed to solve these business process deficiencies, which were focused on fixing business processes to ensure systematic solutions are applied for sustainable results long into the future.Keywords: Concentrator Direct Production Cost, FMEA for Cost, Pareto Analysis for Cost, Grinding Balls CostÂ